Subsurface damage in polishing–annealing processed ZnO substrates. (October 2017) - Prozheeva, V.; Johansen, K.M.; Neuvonen, P.T.; Zubiaga, A.; Vines, L.; Kuznetzov, A.Yu.; Tuomisto, F.
Abstract: Positron annihilation spectroscopy and secondary ion mass spectrometry have been applied to study the evolution of polishing-induced defects in hydrothermally grown ZnO samples depending on the annealing temperature. Annealing of the as-grown ZnO wafer at 1200–1500 °C is found to lead to Li accumulation in the sub-surface layer, and significant reduction of Li content in the bulk. Polishing is shown to introduce vacancy complexes involving both V Zn and V O . Post-polishing annealing of hydrothermally grown ZnO with removed Li layer at 800 ° C reduces the concentration of polishing-induced defects below the detection limit.